Involvement of Inositol Biosynthesis and Nitric Oxide in the Mediation of UV-B Induced Oxidative Stress - Lytvyn, Dmytro I.; Raynaud, Cécile; Yemets, Alla I.; Bergounioux, Catherine; Blume, Yaroslav B. (Frontiers in Plant Science, 2016)
The involvement of NO-signaling in ultraviolet B (UV-B) induced oxidative stress (OS) in plants is an open question. Inositol biosynthesis contributes to numerous cellular functions, including the regulation of plants tolerance to stress. This work reveals the involvement of inositol-3-phosphate synthase 1 (IPS1), a key enzyme for biosynthesis of myo-inositol and its derivatives, in the response to NO-dependent OS in Arabidopsis. Homozygous mutants deficient for IPS1 (atips1) and wild-type plants were transformed with a reduction- grx1-rogfp2 and used for the dynamic measurement of UV-B-induced and SNP (sodium nitroprusside)-mediated oxidative stresses by confocal microscopy. atips1 mutants displayed greater tissue-specific resistance to the action of UV-B than the wild type. SNP can act both as an oxidant or repairer depending on the applied concentration, but mutant plants were more tolerant than the wild type to nitrosative effects of high concentration of SNP. Additionally, pretreatment with low concentrations of SNP (10, 100 μM) before UV-B irradiation resulted in a tissue-specific protective effect that was enhanced in atips1. We conclude that the interplay between nitric oxide and inositol signaling can be involved in the mediation of UV-B-initiated oxidative stress in the plant cell.